Nursing care postpartum women using the Horta's theory and INCP - Maria Clerya Alvino Leite; Ana Lúcia de Medeiros; Maria Miriam Lima da Nóbrega; Maria das Graças Melo Fernandes (Universidade Federal do Ceará, 2013)
This is a case study based on the Theory of Basic Human Needs of Horta, with the aim to operationalize the nursing process to a postpartum anemia. For collect data, we used a script adapted to psychobiological, psychosocial and psycho spiritual needs. For the identification of nursing diagnoses was used to ICNP®, establishing nursing outcomes and interventions that were implemented and evaluated. From psychobiological and psychosocial needs of affected puerperal women were identified in the following diagnoses: impaired oral hygiene, moderate pain, breast engorgement, nipple trauma, constipation, and solitude. It is concluded that the implementation of the nursing process with postpartum anemia was directed to the problems of breastfeeding and their management and improving the quality of life.